Machiavelli a biography - Unger, Miles (New York, NY Simon & Schuster, 2011)
Examines the life of the Florentine intellectual, his relationships with contemporaries ranging from Leonardo da Vinci and Michelangelo to Cesare Borgia and Pope Alexander VI, his philosophies about power, and the legacy of The Prince.
The malice of fate -- Born in poverty -- A sword unsheathed -- The civil servant -- Sir Nihil -- Exit the dragon -- Men of low and poor estate -- The stars align -- Reversal of fortune -- Dismissed, deprived, and totally removed -- The Prince -- Vita contemplativa -- The sage of the garden -- Nightmare and dream -- Finger of Satan.
Includes bibliographical references (p. [353]-386) and index.
Keywords: Machiavelli, Niccolo? -- 1469-1527.; Statesmen -- Italy -- Biography; Intellectuals -- Italy -- Biography; Political scientists -- Italy -- Biography; Authors, Italian -- Biography; Italy -- History -- 1492-1559 -- Biography; Florence (Italy) -- History -- 1421-1737 -- Biography